Key Areas of Corporate Renewal of Polish Enterprises during Crisis of Growth - Bełz, Grzegorz; Wierzbic, Arkadiusz (Kluczowe obszary strategicznej odnowy polskich przedsiębiorstw podczas kryzysu wzrostu, 2010)
The purpose of the article is to present conclusions from the analysis of organizational problems in Polish enterprises which encounter the crisis of autonomy or the crisis of control according to the Greiner's model of organizational growth. The central issue of consideration is the focus on business model change, which takes place in crisis phases. This change is analysed from the perspective of strategic renewal of the enterprise/ company. The conclusions drawn from case studies underline the crucial meaning of changes in management systems, which are the key area of business model evolution.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 93-107
Keywords: crisis of growth; corporate renewal; business model